(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The meaning of accuracy and precision varies in different fields within professional terminology due to the unique requirements of each field. In scientific research, accuracy and precision are essential to obtain reliable data that support scientific theories and technological developments. High-precision instruments and measurement techniques allow scientists to discover new phenomena and reliably confirm existing theories. Accurate data is essential for making informed decisions about environmental protection policies, public health measures and technological innovation.